In-lab simulation of CAD/CAM milling of lithium disilicate glass-ceramic specimens: Effect on the fatigue behavior of the bonded ceramic - Pilecco, Rafaela Oliveira; Dalla-Nora, Fernanda; Guilardi, Luís Felipe; Pereira, Gabriel Kalil Rocha; de Andrade, Guilherme Schmitt [UNESP]; de Melo, Renata Marques [UNESP]; Valandro, Luiz Felipe; Rippe, Marília Pivetta (Elsevier, 2021)
The aim of this study was to evaluate the effect of in-lab simulation procedures performed on a lithium disilicate ceramic luted to a dentin-analogue material regarding the fatigue performance and topographic changes. Lithium disilicate ceramic (IPS e.max CAD) discs (Ø = 13.5 mm and 1.5 mm of thickness) were produced in different ways: milled in a CAD/CAM system (CAD/CAM – control group); mirror-polished (POL group); produced in-lab and ground with #60 silicon carbide paper (SiC group); with #60 wood sandpaper (WS group); with a fine diamond bur (DB group); or with a CAD/CAM bur adapted in a handpiece with a custom mandrel (MANDREL group). The ceramic discs were adhesively luted (Multilink N) onto dentin analogue discs (Ø = 12 mm and 2 mm of thickness) and fatigue testing (n = 19 discs) was performed by step-stress methodology (initial load of 200 N; step-size of 50 N; 10,000 cycles per step; 20 Hz). Surface roughness and contact angle analysis were also performed. According to Kaplan-Meier and post-hoc Mantel-Cox (log-rank), distinct fabrication methods affected the fatigue performance of bonded glass-ceramic discs (p< 0.001). The CAD/CAM group presented the lowest fatigue failure loads (1250 N) and number of cycles for failure (185,000), while the POL groups obtained the highest results (1752 N; 284,444 cycles). The in-lab groups had intermediate values (1355 – 1526 N; 206,052 – 238,684 cycles). Polished specimens presented the lowest roughness values (Ra = 0.041 μm), while the SiC (1.604 μm), WS (1.701 μm), and MANDREL (1.867 μm) groups showed statistically similar roughness values to the CAD/CAM group (1.738 μm). Despite differences before etching, the contact angle was similar among the milled and simulated groups after etching, except for the polished group. Even with some topographic similarities, the tested in-lab simulation methods were not able to mimic the milled specimens in terms of fatigue findings, leading to distinct magnitude of overestimations of the results.
Keywords: Bonding; Computer-aided design/computer-aided manufacturing; Grinding; Lithium disilicate; Mechanical behavior; Surface properties; Survival probability